Polyfunctionality of the CXCR4/CXCL12 axis in health and disease: Implications for therapeutic interventions in cancer and immune‐mediated diseases. Issue 4 (14th March 2021) - Britton, C.; Poznansky, M. C.; Reeves, P.
Abstract: Historically the chemokine receptor CXCR4 and its canonical ligand CXCL12 are associated with the bone marrow niche and hematopoiesis. However, CXCL12 exhibits broad tissue expression including brain, thymus, heart, lung, liver, kidney, spleen, and bone marrow. CXCR4 can be considered as a node which is integrating and transducing inputs from a range of ligand‐receptor interactions into a responsive and divergent network of intracellular signaling pathways that impact multiple cellular processes such as proliferation, migration, and stress resistance. Dysregulation of the CXCR4/CXCL12 axis and consequent fundamental cellular processes, are associated with a panoply of disease. This review frames the polyfunctionality of the receptor at a molecular, physiological, and pathophysiological levels. Transitioning our perspective of this axis from a single gene/protein:single function model to a polyfunctional signaling cascade highlights the potential for finer therapeutic intervention and cautions against a reductionist approach.